Citra Perempuan dalam Karya Sastra Peranakan Tionghoa - Anung Nugroho; Danang Try Purnomo (UIN Raden Mas Said Surakarta, 2018)
Tionghoa literature is a literary work in the Indonesian language produced by Chinese people who were born in Indonesia. In the literary treasures of Indonesia, its literary works are still marginalized. Studies of Chinese literary works are also small. Therefore, the authors challenged to examine some literary works produced by peranakan citizens. As for the literary work of peranakan which is the source of this study data are three novels. The novel is (1) Lo Fen Koei (hereinafter abbreviated LFK) by Gauw Pe Liang, (2) Nyai Soemirah Story (hereinafter abbreviated as CNS) by Thio Tjin Boen, and (3) Flower Roos from Djikembang (hereinafter abbreviated BRDD) by Kwee Tech Hoay. The focal point of this research lies in the views or judgments of the novel authors on indigenous women. To help explore the novel, the author uses two research approaches namely, structural and sociological literature.